Improving the Quality of Santri Graduates at Pondok Pesantren Through Curriculum Management - Farasi, Alexander Desville; Hanum, Azizah; Zein, Achyar (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this research is to determine the planning, organization, and implementation of curriculum management in improving the quality of student graduates at the Hidayatullah Islamic Boarding School Nias. This study employs a qualitative method in conjunction with a descriptive method. However, the collection techniques used interview, observation, and document study techniques, while the researchers referred to the use of data validity standards consisting of credibility, transferability, dependability, and confirmability to strengthen the validity of the data found and the authenticity of the research. Then, what does Hidayatullah Niaster Islamic Boarding School want to achieve in terms of the quality of its graduates, and how will it achieve it through a planning program? Organizing is accomplished through the grouping of student learning, staff, teacher councils, and the distribution of teacher hours that are appropriate for each teacher's abilities.